Effect of health education intervention on personal hygiene Knowledge, attitudes, and practices among food handlers in a tertiary care hospital in New Delhi - Chauhan, Saurabh; Parashar, Mamata; Khandekar, Jyoti (Indian Journal of Community Health, 2024)
Introduction: Food is critical determinant of health, nutritional status and longevity of population. Personal hygiene forms an important domain of food safety to prevent food-borne illnesses. Health education intervention is one of the most effective tools to improve personal hygiene practices to ensure that food is suitable for customers with food safety requirements. Material and methods: This before and after interventional study was conducted among 111 food handlers in food establishments in tertiary care hospital in Delhi. Data collection was done using an interview schedule and observational checklist on personal hygiene based on WHO 5 keys and FSSAI guidelines. Health education intervention included health talks using flipchart, audio-visual aids and demonstration. Endline assessment was done 2 months after intervention. Results: Mean scores regarding personal hygiene knowledge before and after the intervention were 2.69 ± 0.90 and 9.64 ± 0.47 (p=0.046), attitudes before and after the intervention were 2.80 ± 1.15 and 5.77 ± 0.41 (p=0.049) and practices before and after the intervention were 3.23 ± 0.74 and 7.21 ± 0.75 (p= 0.007) respectively with statistically significant changes. Conclusions: Personal hygiene practices of food handlers showed remarkable improvement after health education intervention. Thus, education on food safety in medical institutions needs to be meticulously planned and held at periodic intervals to achieve the desired change.